In the Forest Nature's Footprints - Q. L. Pearce; RGA Publishing Group; W. J Pearce (U.S.A Silver Press, 1990)
The reader is invited to follow animal tracks and observe the habits and habitat of several forest animals.
Keywords: Life on Land